2010
DOI: 10.1016/j.actbio.2009.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of incorporation of zinc into hydroxyapatite

Abstract: The atomic level mechanism of incorporation of Zn(2+) into hydroxyapatite (HAp), which is a potential dopant to promote bone formation, was investigated, based on first principles total energy calculations and experimental X-ray absorption near edge structure (XANES) analyses. It was found that Zn(2+)-doped HAp tends to have a Ca-deficient chemical composition and substitutional Zn(2+) ions are associated with a defect complex with a Ca(2+) vacancy and two charge compensating protons. Moreover, first principle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
88
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(97 citation statements)
references
References 27 publications
8
88
1
Order By: Relevance
“…The X-ray absorption fine structure (XAFS) technique is very useful to analyze the local coordination environment of the substituted atoms. The XAFS results prove that Zn 2+ inside HAP has a single coordination environment and the coordination number is close to 4 [24]. It is suggested that zinc favors to substitute in the Ca2 site over the Ca1 site in HAP according to DFT modeling [22].…”
Section: Introductionmentioning
confidence: 84%
“…The X-ray absorption fine structure (XAFS) technique is very useful to analyze the local coordination environment of the substituted atoms. The XAFS results prove that Zn 2+ inside HAP has a single coordination environment and the coordination number is close to 4 [24]. It is suggested that zinc favors to substitute in the Ca2 site over the Ca1 site in HAP according to DFT modeling [22].…”
Section: Introductionmentioning
confidence: 84%
“…The chemical composition of nHAp is complicated in reality, however the general chemical formula can be presented as formula given in the equation (1) [9]. (1) Precipitated or synthetic hydroxyapatite (sHAp) and calcium deficient hydroxyapatite (CDHAp) are also categorized as Non-Stoichiometric Hydroxyapatite due to formation of vacancies or incorporation of foreign cations or anions in the atomic structure of HAp [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…F − , CO3 2− , Na + , Mg +2 , Zn +2 ) are present in biological apatites [8]. Properties of HA, such as bioactivity, biocompatibility, solubility, and adsorption properties can be tailored over a wide range by modifying the composition via ionic substitutions [9,10].…”
Section: Introductionmentioning
confidence: 99%